The effects of land use conversion on soil organic carbon and selected properties of soils: A case of Nigde province - Selma YAŞAR KORKANÇ; Halil ŞAHİN; Ahmet Onur ÖZDEN; Burak ÖZKURT (Turkish Journal of Forestry, 2018)
The aim of this study was to determine land use change effects on soil organic carbon and some selected soil properties in a land converted from rangeland to fast growing poplar plantation area 15 years ago. Soil samples were taken according to the systematic sampling method in two different land use types; rangeland and poplar plantation. 12 of disturbed and 12 of undisturbed (using 100 cm3 bulk steel cylinders) topsoil samples (0-20 cm depth) were taken from each land use types. Soil samples were analyzed for particle size distribution (texture), particle density, pH, electrical conductivity, organic carbon, aggregate stability, bulk density, total porosity, water holding capacity, and dispersion ratio. Data were analyzed by using one way analysis of variance at 95 % significance level. According to results of this study, bulk density, total porosity, pH, organic carbon, aggregate stability, clay, sand, silt and dispersion ratio values of the soils were affected from land use conversion. Soil organic carbon, aggregate stability and total porosity of soils increased whereas bulk density and pH of soils decreased after land cover change from rangeland to poplar plantation area.